A high‐performance empty substrate integrated waveguide filter with mixed electric and magnetic coupling. Issue 4 (4th February 2022) - Qiang, Jingxia; Xu, Feng; Yang, Ling; Liu, Shui; Zhan, Junlin; Li, Min
Abstract: An empty substrate integrated waveguide (ESIW) bandpass filter with enhanced electric and magnetic coupling is proposed in this letter. ESIW uses the air as dielectric in order to reduce the dielectric loss caused by usual medium materials. However, the existence of air cavities requires at least three layers of structure, which greatly increases the difficulty of designing complex circuits with high‐performance and multiple requirements. The proposed mixed coupling structure creates the finite transmission zeros based on ESIW technology for the first time, which makes it possible to realize complex high‐performance circuits with ESIW technology. Taking advantage of the multilayer structure of the ESIW, the proposed cross‐coupling is conveniently realized with higher frequency selectivity and lower insertion loss while maintaining the substrate of three layers and the self‐encapsulation characteristics of ESIW. A fourth‐order filter with an H‐shaped slot line on the top metal plane of two adjacent air cavities is produced. A good agreement between the measurements and simulations indicates that the proposed filter achieves an insertion loss as low as 0.7 dB and the 6.1% bandwidth at 9.85‐GHz X band. It demonstrates the improvement of insertion loss and frequency selectivity, which lays a foundation for the design of complex microwave devices.